2002
DOI: 10.1152/japplphysiol.00500.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and metabolic responses to hypoxia in the smallest simian primate, the pygmy marmoset

Abstract: Tattersall, Glenn J., James L. Blank, and Stephen C. Wood. Ventilatory and metabolic responses to hypoxia in the smallest simian primate, the pygmy marmoset. J Appl Physiol 92: 202-210, 2002; 10.1152/japplphysiol.00500.2001.-The pygmy marmoset (Cebuella pygmaea) is the smallest New World Monkey (average body mass of 120-130 g). As such, it faces possible challenges to thermoregulation. Small mammals (e.g., rats) are well known to lower body temperature and metabolism in response to hypoxia; however, small prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(49 reference statements)
8
11
0
Order By: Relevance
“…Gordon (1997) measured heat loss in hypoxic rats with direct calorimetry, and demonstrated that heat loss increased and remained elevated above heat production for nearly an hour in hypoxia. Similar results were observed in a small primate breathing 10% O2 (Tattersall et al, 2002), although the duration of elevated heat loss was shorter, reflecting the more G. J. Tattersall modest decrease in Tb in the primate (only 2°C versus a 4-5°C drop in the rat).…”
Section: Co∑supporting
confidence: 80%
“…Gordon (1997) measured heat loss in hypoxic rats with direct calorimetry, and demonstrated that heat loss increased and remained elevated above heat production for nearly an hour in hypoxia. Similar results were observed in a small primate breathing 10% O2 (Tattersall et al, 2002), although the duration of elevated heat loss was shorter, reflecting the more G. J. Tattersall modest decrease in Tb in the primate (only 2°C versus a 4-5°C drop in the rat).…”
Section: Co∑supporting
confidence: 80%
“…In other words, oxygen impacts differently on the various thermoregulatory pathways in the bumblebee and thermolysis occurring prior to metabolic downregulation. This situation is similar to what has been observed in small mammals (Tattersall et al, 2002;Tattersall and Milsom, 2009). Exposure to low O 2 levels, however, does not appear to have a long-term consequence in terms of thermoregulatory ability.…”
Section: Effects Of Oxygen On Body Temperaturesupporting
confidence: 91%
“…Animals from the summer phase showed a hypoxic response similar to that observed in other mammals; decreases in metabolic rate and T b in hypoxia became larger as T a and oxygen levels decreased (Hiestand et al, 1950;Wood, 1995;Barros et al, 2001;Tattersall et al, 2002;Scott et al, 2008). The relationship between T a , metabolic rate and T b is consistent with a reduction in thermogenesis in hypoxia, accompanied by a selection of lower temperatures, leading to a temperature-dependent decrease in T b .…”
Section: Discussionsupporting
confidence: 71%
“…Hibernating species are known to survive periods of anoxia for longer than nonhibernating species (Lutton, 1982) and have a more moderate physiological response when confronted with a hypoxic stress (Faleschini and Whitten, 1975). A common hypoxic response that small mammals and other vertebrates exhibit, whether they hibernate or not, is a rapid and reversible decrease in body temperature (T b ) and metabolic rate (Wood, 1995;Wood and Gonzales, 1996;Tattersall et al, 2002;Tattersall and Milsom, 2003). The higher tolerance to hypoxia in hibernators does not necessarily dictate the magnitude of this thermoregulatory response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%